Pessoa com deficiência física na atenção primária em saúde: necessidades dos usuários e prática profissional dos terapeutas ocupacionais - NOVAIS, Tatyani Arícia Maia (2023)
This study aimed to identify the health and occupational needs of people with physical disabilities (DF) and to understand the professional practice of occupational therapists who work at the Family Health Support Centers (NASF) in the city of Belém/PA. The method was based on the qualitative approach with a descriptive approach, of transversal character and non-probabilistic sampling of the type for convenience. The research was conducted in the city of Belém, Pará, considering the division of administrative districts in which the municipality is organized. Data were collected during the period from July to November 2017, through semi-structured interviews with DF in the age group between 18 and 59 years, residents of the city of Belém and occupational therapists linked to NASF in the city. The results showed 4 categories associated to the participants' perceptions about the health and occupational needs of DF, the participation of this public in the territory and the professional practice of occupational therapists. Regarding health needs, categories related to life scenario, access to health services and functional impairment emerged. Regarding occupational needs, aspects related to caring for oneself, socialization, involvement in work and sense of doing have arisen. Participation was illustrated by DFs who used the health services of their community and those who were restricted to the home characterizing a weak social network. Regarding the work of the occupational therapist, direct and indirect actions for DF were reported, such as home visits, referrals, adaptations, partnerships, health education and training. Within this work process, many obstacles were encountered, related to structural challenges, difficulties in network effectiveness and work dynamics - involving interpersonal relationships and occupational difficulties. It was concluded that the study favored a better understanding of the health and occupational needs of the DF, evidencing that some demands of this public can be accepted in primary care, and that in most cases, DF fail to accomplish what they want or choose to do, thus presenting an occupational gap present in their daily lives. It was also noted that the use of basic care services is fundamental for the exercise of the right of access to health, and that the difficulties encountered by professionals in the development of their actions interfere with the assistance offered, as well as the emergence of possible situations of diseases.